2021
DOI: 10.51253/pafmj.v71i4.4136
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Extraperitoneal and Transperitoneal Radical Cystoprostatectomy in Terms of First 30 Days Outcomes

Abstract: Objective: To compare the first 30-day outcomes of Trans-peritoneal and Extra-peritoneal Radical cysto-prostatectomy. Study Design: Quasi-experimental study. Place and Duration of Study: Armed Forces Institute of Urology, Rawalpindi, from Mar 2015 to Mar 2019.Methodology: A total of 100 patients who underwent Radical cystoprostatectomy were observed in two groups either by extra or trans-peritoneal approach. Patients diagnosed with carcinoma urinary bladder (both muscle and non-muscle invasive) vet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Soleimani, et al claimed that early GI complications were lower in EPRC groups, including oral intake intolerance (21 vs. 8, p = 0.04), ileus (19 vs. 8, p = 0.04), intestinal obstruction (3 vs. 0, p = 0.04), and anastomosis leakage (8 vs. 1, p = 0.01) [12]. Several other studies also concluded similar results [13,14]. In this meta-analysis, we found no significant difference related to major complications occurring after EPRC or TPRC surgery.…”
Section: Plos Onementioning
confidence: 85%
See 2 more Smart Citations
“…Soleimani, et al claimed that early GI complications were lower in EPRC groups, including oral intake intolerance (21 vs. 8, p = 0.04), ileus (19 vs. 8, p = 0.04), intestinal obstruction (3 vs. 0, p = 0.04), and anastomosis leakage (8 vs. 1, p = 0.01) [12]. Several other studies also concluded similar results [13,14]. In this meta-analysis, we found no significant difference related to major complications occurring after EPRC or TPRC surgery.…”
Section: Plos Onementioning
confidence: 85%
“…Because of these multifactorial reasons that could alter the hospitalization time, is not out of the ordinary that high heterogeneity is found (I 2 = 96%) between the studies included. However, two authors have claimed that the duration of patient stay is significantly lower EPRC group [ 3 , 14 ]. Özkaptan et al and Soleimani et al, also concur that the mean length of hospital stay is shorter in the EPRC group, although not significant [ 5 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation